2013
DOI: 10.5603/njo.2013.0035
|View full text |Cite
|
Sign up to set email alerts
|

Identyfikacja i znaczenie krążących endotelialnych komórek progenitorowych u chorych na raka wątrobowokomórkowego

Abstract: Cel badań. Badania poświęcono identyfi kacji i ocenie znaczenia endotelialnych komórek progenitorowych we krwi obwodowej chorych na HCC. Materiał i metoda. Badania przeprowadzono u 133 chorych na HCC, dotychczas nieleczonych, z których 46 zostało zakwalifi kowanych do resekcji wątroby, 45 do przeszczepienia wątroby i 42 do leczenia paliatywnego. Grupę kontrolną stanowiło 43 osób zdrowych i 42 chorych na marskość wątroby, bez stwierdzonego raka. Od badanych pobierano próbki świeżej krwi w objętości 2 ml i niezw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Gradual changes of both these biomarkers are also observed in Child's B and C patients with liver cirrhosis as compared to those in Child's A. The results confirmed the suggestions of the potential clinical utility encouraged by the others [10,12,20,22].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Gradual changes of both these biomarkers are also observed in Child's B and C patients with liver cirrhosis as compared to those in Child's A. The results confirmed the suggestions of the potential clinical utility encouraged by the others [10,12,20,22].…”
Section: Discussionsupporting
confidence: 79%
“…The study conducted on 133 patients with HCC showed that the rates of hematopoietic stem cells, as well as the rates of endothelial progenitor cells, increase in the peripheral blood circulation of patients with liver cirrhosis, reaching the highest level in patients with HCC, in comparison to the volunteers with a healthy liver. Moreover, it was shown that the rate of hematopoietic stem cells within the white blood cells (%HSCs/WBC) gradually increases whereas the rate of Endothelial Progenitor Cells within the fraction of Hematopoietic Stem Cells (%EPCs/HSCs) gradually decreases depending on the stage of clinical tumor development [19,20]. Both cell fractions are known as the timber for tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation